Highly Dispersed Layered Double Hydroxide Crystals onto Carbon Nanotubes and its Catalytic Properties in Benzaldehyde Oxidation - Lei Liu, Xiao; Wang, Qian; Qiu Zhao, Nai; Wei, Min; Duan, Xue (Asian Journal of Chemistry, 2011)
Nickel aluminum layered double hydroxide (LDH) was dispersed onto the surface of multiwalled carbon nanotubes (MWCNTs) by hydrothermal method and the resulting material shows superior catalytic activity in the oxidation reaction of benzaldehyde.